Estresse, estressores e estratégias de enfrentamento de familiares de mulheres acometidas por câncer de mama - Nascimento, Ariana Nogueira do (2008)
When a family member gets a disease, it provokes alterations in its dynamics, and front to the diagnosis and the treatment of the breast cancer, they face a sequence of tensions that intervene in the familiar unit. To understand this process, this study took place aiming to characterize the women’s with breast cancer families; assess the symptoms of their stress by the level, the frequency and intensity. Then, it was linked the level of stress with the variables of the patient (age, stage level, , type of treatment and length of treatment) and the family (age, sex, colour / race, marital status, educational background, origin, religion, occupation, degree of relationship and previous experience of a member affected by cancer). We also aim to describe the stressors and identify strategies for confronting these families. This is an exploratory-descriptive study, developed in the Ilza Bianco Ambulatory - Hospital Santa Rita de Cássia, in particular PREMMA in Vitoria-ES, between August and December 2007, with 200 women’s with breast cancer relatives.The instruments used were the Patient and Family Characterization Inventory, the List of Symptoms of Stress (LSS/VAS), Description of Stressors, and, Coping Strategies Inventory of Lazarus and Folkman. To find out the quantitative data it was used the descriptive analysis by listing percentage calculations, median, average and standard deviation. With the help of SPSS version 11.0, it was applied the Chi-Square Test and the Fisher Test for verifying statistics relations between the Women and Families´ variables and the level of stress. As for the Qualitative Data Analysis it was used the Collective Subject Speech Method. We draw conclusions from the results showed: the families’ characteristics are similar to the customers´ profile of the public health. The level of stress was medium/high and there was a statistically significant relationship between the level of stress and patient length of treatment as well as the race / colour and previous experience from a relative. The most frequent and intense symptoms were found within the cognitive, behavioural and social spheres and least frequent and intense within the physiological sphere. The stressors were the announcement of the breast cancer to the family, the cancer as a sentence of death, the surgery, the adverse effects of chemotherapy medication, the uncertainty of the treatment outcome / healing, the coexistence with the one’s illness, the loneliness caused by the one’s cancer, and conditions of the National Heath Service. Coping strategies used by family members are more focused on the problem and few strategies used are focused on emotion, showing that they are looking for re-balance their lives. Furthermore, it was concluded front to difficulties the families were being through, that is important to involve them in the treatment process. The health professional has also an important role in order to understand and contextualize the patient and each family member experience, as well as helping them to recognize strategies that decrease stress and stressors.